Influence of Pregelatinized Breadfruit Starch-Alginate Blend as a Sustained Release Polymer in Theophylline Microbeads Using Box Behnken Design (Nigerian Journal of Pharmaceutical Research, 2020)
Background: Apart from the coating property of modified starches on drugs, these natural polymers also acts as release rate retardants.Objectives: To evaluate the potential of pregelatinized breadfruit (Artocarpus altilis) starch as a carrier in microbead formulations of theophylline using different blend combinations with sodium alginate and to determine the optimized formulation using Box-Behnken design.Method: Theophylline microbeads were prepared using the ionic gelation method. The 3 factor-3 level Box-Behnken design was employed for constructing polynomial models to optimize the microbeads, involving 3 independent variables (polymer type, X1, polymer: drug ratio, X2, and concentration of calcium chloride, X3) and 2 dependent variable (entrapment efficiency and quantity of drug released in 12 h, Q12).Results: Entrapment efficiency was 35 - 71 % while the values of Q12 was 38 - 88 %. The three variables, X1, X2 and X3, were positive for entrapment efficiency but negative for Q12, implying that increase from low to medium and then to high level resulted in an increase in entrapment but a decrease in Q12 (sustained release), both desirable effects. Factor X1 had the most significant influence on entrapment efficiency and Q12 (p = 0.002; p = 0.0001, respectively). The optimized formulation with starch:polymer 2:1, polymer:drug 3:1 and 7.5%w/v calcium chloride solution gave an entrapment efficiency 65% with Q12 of 38.75%.Conclusion:  Pregelatinized breadfruit starch enhanced entrapment efficiency while retarding drug release, showing its potential as a polymer for sustained release in microbead formulations.